Burnout among Swedish school teachers – a cross-sectional analysis. (December 2016) - Arvidsson, Inger; Håkansson, Carita; Karlson, Björn; Björk, Jonas; Persson, Roger
Abstract Background Teachers are at high risk of stress-related disorders. This study aimed to examine the occurrence of burnout in a sample of Swedish school-teachers, to test a combined measure of three burnout dimensions on the individual level, to characterize associations between burnout and factors encountered during work and leisure time, and to explore any differences between the genders. Methods A questionnaire of occupational, sociodemographic and life-style factors was answered by 490 teachers in school years 4–9. Outcome measures were (a) the single burnout dimensions of exhaustion, cynicism and professional efficacy (Maslach Burnout Inventory-General Survey), and (b) a combined measure based on high or low values in the three dimensions. The combined measure was used to stratify the study population into four levels (0–3) of burnout. Multivariable Poisson regression was applied on level 2 + 3 vs. level 0 + 1, for variables that we considered as relevant risk factors for burn out. Results Half of the teachers reported low values in all three dimensions (level 0), whereas 15 were classified as having high burnout in at least two out of the three dimensions (level 2 + 3), and 4 % in all three dimensions (level 3). Almost all psychosocial factors were incrementally more unfavourably reported through the rising levels of burnout, and so were dissatisfaction with the computer workstation, pain, sleep problems and lack of personal recovery. There was no association between gender and rising levels of overall burnout (p > 0.30). Low self-efficacy, poor leadership, high job demands and teaching in higher grades were the variables most clearly associated with burnout in multivariable Poisson regression. Conclusions Even if circa 50 % of the teachers appear do well with respect to burnout, the results points to the need of implementing multifaceted countermeasures that may serve to reduce burnout.